First–principle studies on the electronic structural, thermodynamics and elastic properties of Mg17Al12 intermediate phase under high pressure. (5th June 2019) - Zhou, Yong; Dang, Mohan; Sun, Liang; Zhai, Wenyan; Dong, Hui; Gao, Qian; Zhao, Fei; Peng, Jianhong
Abstract: As an intermediate phase in Mg-Al alloy, Mg17 Al12 has an important role of hindering dislocation motion to strengthen grain boundaries. The influence of pressure on the structural properties, electronic structure, and mechanical properties of Mg17 Al12 from 0 GPa to 8 GPa have been investigated by using first-principles calculations. As the pressure increases in the pressure range, Mg17 Al12 intermediate phase stay thermodynamic stable. Based on first-principles calculations study, from band structure analysis, Mg17 Al12 has strong metallic character, and the metallicity of this phase reduced due to applied pressure. Moreover, the ionic bond interaction between Mg and Al atoms increase with increasing pressure. Due to empirical criterion and Cauchy pressure, Mg17 Al12 have a mechanically stable structure as well as brittleness property from 0 GPa to 8 GPa. Generally speaking, after theoretical study, the effect of pressure on Mg17 Al12 improve its compression resistance and fracture resistance, the ability of resisting plastic deformation also becomes stronger. Moreover, appling pressure can weaken the brittleness of Mg17 Al12 . The study of its anisotropy also play an important rule in Mg-Al alloy grain boundary strengthening. Mg17 Al12 exhibits anisotropy at 0 GPa to 8 GPa, and Mg17 Al12 has the strongest stiffness along the ⟨100⟩ direction.